A comparative study of rhetorical imagery in the story of Bahram Gur in Ferdowsi's Shahnameh and Nezami's Haft-Peykar - Fatemeh Shahmoradi; Jamileh Akhyani; Farideh Vejdani (مطالعات زبانی و بلاغی)
Imagery is considered as one of the most important artistic aspects in the literariness of any work of art. This becomes more important in narrative poetry because, if depicted properly, it will encourage the audience and create an emotional response in him to hear the rest of the narration. One of the famous stories of Persian classical literature is the story of Bahram Gur, which is represented both in Ferdowsi's Shahnameh and Nezami's Haft-Peykar. In this article, we have compared the rhetorical imagery concerning this story in the two aforementioned works. To this end, we have examined and compared the imagery created by the two poets in the two categories of “imagery describing actions” and “imagery depicting the setting”. The result of this study shows that, concerning imagery describing actions, there are more action-based and dynamic images in the story of Bahram Gur in Shahnameh than that of Haft-peykar due to the narrative pace of events and actions as well as the high frequency of verbs. With regard to the imagery depicting the settings, Ferdowsi’s version presents more adventurous and plausible images than those created by Nezami. However, images of feasting and battlefield settings are abundantly portrayed in both works.